Dynamics of Spatiotemporal Variation of Groundwater Arsenic in Central Rift Vally of Ethiopia: A Serial Cross-Sectional Study - Solomon Demissie; Seblework Mekonen; Tadesse Awoke; Bezatu Mengistie (SAGE Publishing, 2024)
Background: Arsenic is a well-known, highly poisonous metalloid that affects human health and ecosystems and is widely distributed in the environment. Nevertheless, data on the spatiotemporal distribution of arsenic in groundwater sources in Ethiopia are scarce. Objective: The principal aim of this study was to assess the extent of arsenic in groundwater sources and analyze the spatiotemporal variations in the central rift valley of Ethiopia. Methods: The study employed a serial cross-sectional study design and census sampling methods. The concentrations of arsenic in the groundwater samples were determined using inductively coupled plasma mass spectrometry (ICP-MS) at the Ethiopian Food and Drug Authority laboratory. Descriptive statistical analyses were performed using IBM SPSS version 29 software. Additionally, ArcGIS software was utilized to map the spatiotemporal distribution of arsenic. Furthermore, Minitab statistical software version 21.4 was employed to assess the correlation between spatiotemporal variations of arsenic concentrations in groundwater sources. Results: The mean values of arsenic in the groundwater samples were 11.2 µg/L during the dry season and 10.7 µg/L during the rainy season. The study results showed that 18 wells (42.2%) and 22 wells (48.8%) had higher arsenic concentrations (>10 µg/L) during the dry and rainy seasons, respectively. Thus, arsenic levels in 42.2% and 48.8% of the samples exceeded the maximum threshold limit set by WHO, USEPA, and Ethiopian standards (10 µg/L), respectively, during the dry and rainy seasons. Furthermore, our analysis revealed a significant positive correlation between arsenic in groundwater and well depth ( r  = .75, P  < .001), indicating a strong association between higher arsenic concentrations and deeper wells. Similarly, we observed a substantial positive correlation between arsenic concentration in groundwater and season ( r  = .9, P  < .001), suggesting notable variations in arsenic levels between dry and rainy seasons. Conclusions: The majority of the groundwater sources in the studied area are unfit for human consumption because they contain high amounts of arsenic, which poses a significant risk to human health. Moreover, the arsenic concentration varied spatially and temporally. Therefore, special attention is needed to reduce arsenic exposure and associated health risks.